2016
DOI: 10.1073/pnas.1522034113
|View full text |Cite
|
Sign up to set email alerts
|

Importance of ocean salinity for climate and habitability

Abstract: Modeling studies of terrestrial extrasolar planetary climates are now including the effects of ocean circulation due to a recognition of the importance of oceans for climate; indeed, the peak equatorpole ocean heat transport on Earth peaks at almost half that of the atmosphere. However, such studies have made the assumption that fundamental oceanic properties, such as salinity, temperature, and depth, are similar to Earth. This assumption results in Earth-like circulations: a meridional overturning with warm w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 36 publications
0
44
0
Order By: Relevance
“…The Earth's thermohaline circulation was recently placed into perspective by Cullum & Stevens (2016) who demonstrated that an increase in mean salinity can cause the haline component to dominate.…”
Section: Dynamic Coupled Oceanmentioning
confidence: 99%
“…The Earth's thermohaline circulation was recently placed into perspective by Cullum & Stevens (2016) who demonstrated that an increase in mean salinity can cause the haline component to dominate.…”
Section: Dynamic Coupled Oceanmentioning
confidence: 99%
“…Experiments b – h are identical to a except that the salinity initial conditions and surface forcing are multiplied by a constant factor ξ between 0 and 3. Salinity is shifted in this way to maintain relative salinity differences while changing the mean salinity [ Cullum et al , ].…”
Section: Methodsmentioning
confidence: 99%
“…Investigating the habitability of exoplanets, Cullum et al [] used a box model to test for the impact of mean salinity on an idealized ocean circulation. As freshwater at surface pressure has a nearly quadratic equation of state with respect to temperature, they used a quadratic function for ρ ( T ) to test the case where trueS̄=0.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations